A review of the minimum wrestling weight procedures used in American scholastic wrestling - Curby, D. G. (International Journal of Wrestling Science, 2012)
The National Federation of High Schools (NFHS) established a rule for wrestling (1-3-1) that each individual state high school association shall develop and utilize a specified weight-control program which will discourage excessive weight reduction. Programs must establish a minimum weight class through hydration testing, body fat assessment and a monitored descent plan. Purpose: A survey of the 49 state associations conducting high school wrestling programs was made to determine the methods used for the 2010-11 season to assess hydration status and body composition, as well as the administrative procedures employed to meet this weight management mandate. Methods: Information was obtained from state association websites, which was followed by phone interviews with state administrators. Results: Multiple methods are approved for use in the majority of programs. Urine specific gravity to assess hydration is tested by a refractometer (33 states), reagent strip (28 states), urinometer/hydrometer (6 states), color chart (5 states), and is not tested in 4 state programs. Body fat is assessed through caliper measures of skinfolds (35 states), bioelectric impedance (24 states), hydrostatic weighing (21 states), air displacement plethysmography (12 states), physician observation (7 states), DXA (4 states), ultrasound (3 states), near infrared interactance (1 state), and one program does not consider body fatness. 36 states utilize the National Wrestling Coaches Association Optimal Performance Calculator™ to manage their program. Many states apply a variance to the recommended weight at the body fat minimums of 7% and 12% for males and females respectively, ranging from a 0.9 to 5% reduction in these values. For males in the 35 programs utilizing skinfold measures, 34 use the Lohman equation, and 1 uses the Forsyth-Sinning equation. For females, the Boileau equation is used in 32 programs, the Jackson, Pollock, and Ward equation is used in one program, and two programs are inappropriately using equations developed for use by males, with the females. In programs utilizing bioelectric impedance, 12 use the standard setting while 12 the athletic setting. Conclusions: A discussion of the variations observed in the methods and procedures employed in weight control programs among sport science professionals, as well as the state associations and the National Federation can further improve scholastic wrestling.